The epic game of creating a successful gamified co-creation strategy - Jo\~ao Lopes; Sofia Gomes; Nélia Santos; Hugo Cussina; Isabel Vieira; Maria Escudeiro; Lissandra Maio; Yolanda Magalh\~aes (Administrative Sciences, 2023)
This paper aims to explore consumer engagement with online retailers through gamification, the use of game mechanics, and co-creation. A qualitative methodology was used through an exploratory case study approach. The interviews were conducted with 30 Portuguese consumers. It was found that the majority of respondents do not consider online shopping as a substitute for other entertainment activities. Respondents stressed that in online shopping, the important thing is personal satisfaction and their needs. According to the Hexad model, these characteristics fit the free spirit gamer, the Barttle model the explorer and the BrainHex model the seeker. As far as co-creation is concerned, the results indicate that most of the interviewees do not value the tools that exist on the retailers' websites which allow them to create their own product. This study provides recommendations for retailers to implement a successful co-creation gamification strategy. Companies need to include gaming elements to enhance the retail experience and increase sales. In turn, this can increase competitive pressures among retailers by improving the services and products they offer. This paper provides empirical support for the current dearth of qualitative studies on the role of gamification and co-creation in the online retail experience. Many of the findings of this study are not in line with existing literature, allowing the conclusion that gamification alone is no longer enough to engage the online retail consumer with products and brands, requiring co-creation for the effective engagement of this consumer.
Keywords: 350; co-creation; ecommerce; gamification; online retail experience; online shopping